Development and Validation of a Mortality Risk Prediction Index Score for Adults Living with HIV and Multiple Chronic Comorbidities - Viviane Dias Lima; Bronhilda Takeh; Neil Faught; Hasan Nathani; Jielin Zhu; Scott Emerson; Katerina Dolguikh; Jason Trigg; Kate Salters; Rolando Barrios; Julio Montaner (International Journal of Population Data Science)
Introduction Aging while living with HIV poses new challenges in clinical management, mainly due to the onset of multiple chronic comorbidities. Population-specific risk prediction indices considering comorbidities and other risk factors are essential to comprehensively characterise disease burden among PLWH. We developed and validated a mortality risk prediction index i to predict the risk of one-year all-cause mortality among people living with HIV (PLWH).